Nuclear and radiochemistry : fundamentals and applications - Lieser, Karl Heinrich; Wiley InterScience (Online service) (Berlin ; New York : Wiley-VCH, 2001)
This new edition of the best-selling handbook gives a complete and concise description of the latest knowledge on nuclear and radiochemistry as well as their applications in the various fields of science. It is based on over 40 years experience in teaching courses and research. The book is aimed at all researchers seeking sound knowledge about the properties of matter, whether chemists, physicists, medical doctors, mineralogists or biologists. All of them will find this a valuable source of information. Research in radiochemistry includes: Study of radioactive matter in nature, investigation o.
Nuclear and Radiochemistry; Preface; Contents; 1 Radioactivity in Nature; 2 Radioelements, Isotopes and Radionuclides; 3 Physical Properties of Atomic Nuclei and Elementary Particles; 4 Radioactive Decay; 5 Decay Modes; 6 Nuclear Radiation; 7 Measurement of Nuclear Radiation; 8 Nuclear Reactions; 9 Chemical Effects of Nuclear Reactions; 10 Influence of Chemical Bonding on Nuclear Properties; 11 Nuclear Energy, Nuclear Reactors, Nuclear Fuel and Fuel Cycles; 12 Production of Radionuclides and Labelled Compounds; 13 Special Aspects of the Chemistry of Radionuclides; 14 Radioelements.
'Chart of the nuclides' in pocket.
Includes bibliographical references and indexes.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Nuclear chemistry; Radiochemistry; SCIENCE -- Chemistry -- Physical & Theoretical; Nuclear chemistry; Radiochemistry; Química nuclear; Electronic books